Falsafah alam dalam konteks falsafah ketuhanan menurut Hamka - Zul' Azmi Yaakob (Universiti Kebangsaan Malaysia, 2012)
Islam via al-Quran strongly stresses the significant existence of nature. The creation of universal nature is considered as ultimate proof of the existence of God, the Creator. Islamic philosophers or religious thinkers tend to relate the significance of nature with living an appreciative life. Hamka on his philosophy of nature relates the creation to philosophy of God without distinguishing sharply between philosophy of nature and philosophy of God, calling his position ‘philosophy of life’. He was a prolific Muslim scholar whose influence persists throughout Indonesia, Malaysia, Brunei, Singapore and Southern Thailand. Although Hamka passed away 31 years ago, his philosophy still remained strong in Malay Archipelago because of his greatness. Thus, the aim of this article is to analyze Hamka’s philosophy on nature and its relation to philosophy of God as portrayed in his book Filsafat Ketuhanan (Philosophy of God) and Falsafah Hidup (Philosophy of Life).